2013
DOI: 10.1038/nchembio.1359
|View full text |Cite
|
Sign up to set email alerts
|

Development of small-molecule inhibitors targeting adipose triglyceride lipase

Abstract: Adipose triglyceride lipase (ATGL) is rate-limiting in the mobilization of fatty acids from cellular triglyceride stores. This central role in lipolysis marks ATGL as interesting pharmacological target since deregulated fatty acid metabolism is closely linked to dyslipidemic and metabolic disorders. Here we report on the development and characterization of a small-molecule inhibitor of ATGL. Atglistatin is selective for ATGL and reduces fatty acid mobilization in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
189
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(197 citation statements)
references
References 25 publications
7
189
0
Order By: Relevance
“…Based on our results, the most parsimonious explanation for the abnormal lipid peak observed by cerebral magnetic resonance spectroscopy in human subjects with DDHD2 mutations (6) is that it reflects elevated TAGs, although it remains possible that DDHD2 could regulate distinct classes of lipids in the mouse and human brain. We also cannot explain, at present, why subchronic treatment with a DDHD2 inhibitor is needed to produce TAG elevations in the mouse brain, but we should note that acute treatment with an ATGL inhibitor also causes more limited changes in TAGs in peripheral tissues compared with chronic (genetic) disruption of ATGL (22,33). Projecting forward, it will be important to evaluate how deregulated TAG metabolism and LD accumulation affect neuronal cell biology and, ultimately, HSP neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, the most parsimonious explanation for the abnormal lipid peak observed by cerebral magnetic resonance spectroscopy in human subjects with DDHD2 mutations (6) is that it reflects elevated TAGs, although it remains possible that DDHD2 could regulate distinct classes of lipids in the mouse and human brain. We also cannot explain, at present, why subchronic treatment with a DDHD2 inhibitor is needed to produce TAG elevations in the mouse brain, but we should note that acute treatment with an ATGL inhibitor also causes more limited changes in TAGs in peripheral tissues compared with chronic (genetic) disruption of ATGL (22,33). Projecting forward, it will be important to evaluate how deregulated TAG metabolism and LD accumulation affect neuronal cell biology and, ultimately, HSP neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…The Atgl / mice also provided a model to study the specificity of the ATGL-specific inhibitor, Atglistatin, in HSCs (22). Surprisingly, Atglistatin treatment for 6 days resulted in an almost similar increase in TAG levels in Atgl / HSCs as compared with WT HSCs (Fig.…”
Section: Atglistatin Inhibits the Predominant Lipase In Mouse Hscsmentioning
confidence: 97%
“…3). This would eliminate monoglyceride lipase, HSL, lipoprotein lipase, and pancreatic lipase, as well as PNPLA6 and PNPLA7, which were shown to be unaffected by this drug (22). PNPLA3, also called adiponutrin (ADPN), is also an unlikely candidate because this enzyme is involved in TAG remodeling, rather than in net lipolysis (26).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on serine hydrolase inhibitors ( 18 ) using rodent tissues showed that WWL64 is a specifi c inhibitor of patatin-like phospholipase domain containing 2 /ATGL. Another study ( 17 ) reported ( 20 ), and also hCES1 ( Tables 1 and 2 ). The widely used DAGL inhibitor, RHC20867, actually barely inhibited hDAGL ␣ at 5 M but inhibited hHSL, hMAGL, hABHD6, and hCES1 to different degrees ( Table 1 ).…”
Section: Abhd6 Activity and Inhibitionmentioning
confidence: 99%